Overdot and overline annotation must be understood to accurately interpret V.O2MAX physiology with the Fick formula - Gifford, Jayson R.; Blackmon, Christina; Hales, Katelynn; Hinkle, Lee J.; Richards, Shay (Frontiers in Physiology, 2024)
Few formulas have been used in exercise physiology as extensively as the Fick formula, which calculates the rate of oxygen consumption (i.e., V.O2) as the product of cardiac output (Q.) and the difference in oxygen content in arterial and mixed venous blood (Δav¯O2). Unfortunately, the physiology of maximum V.O2 (V.O2MAX) is often misinterpreted due to a lack of appreciation for the limitations represented by the oft-ignored superscript annotations in the Fick formula. The purpose of this perspective is to explain the meaning of the superscript annotations and highlight how such annotations influence proper interpretation of V.O2MAX physiology with the Fick formula. First, we explain the significance of the overdots above V.O2 and Q., which indicate a measure per unit of time. As we will show, the presence of an overdot above Q. and lack of one above Δav¯O2 denotes they are different types of ratios and should be interpreted in the context of one another—not in contrast to each other as is commonplace. Second, we discuss the significance of the overline above the “v¯” in Δav¯O2, which indicates the venous sample is an average of blood that comes from mixed sources. The mixed nature of the venous sample has major implications for interpreting the influence of oxygen diffusion and blood flow heterogeneity on V.O2MAX. Ultimately, we give recommendations and insights for using the Fick formula to calculate V.O2 and interpret V.O2MAX physiology.